Beyond Israel and Aram: the archaeology and history of Iron Age communities in the central Levant - Kleiman, Assaf (Orientalische Religionen in der Antike, 2022)
"In this study, Assaf Kleiman discusses the settlement history and material culture of complex communities that flourished in the shadow of Israel and Aram-Damascus. A detailed examination of the finds from the Lebanese Beqaa, through the Sea of Galilee, to the Irbid Plateau, offers an exceptional portrayal of the developments experienced by these communities, before and after the emergence of the territorial kingdoms; these advances include the rise and fall of local polities, the adoption and rejection of certain cultural traits, and even the background for the dissemination of writing. The study provides, therefore, a new and exciting way to look at the political relations and cultural exchange between the indigenous communities and the elites that ruled over them. Rather than interpreting the local populations simply as "Israelites" or "Aramaeans," the archaeological record reveals their diversity and highlights the discrete historical trajectories they followed from the 12th to 8th centuries BCE" --